A Five Level Modified Cascaded H-Bridge Inverter STATCOM for Power Quality Improvement - Prashant Kedarnath Magadum; Sangmesh Sakri (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2023)
Multilevel converters have received serious attention on account of their capability of high voltage operation, high efficiency, and low electromagnetic interference. It has many advantages compared to conventional two-level inverters such as high dc-link voltages, reduced harmonic distortion, fewer voltage stresses, and low electromagnetic interferences. The multilevel converters have been used for STATCOM widely as it can improve the power rating of the compensator to make it suitable for medium or high-voltage high power applications. While deploying multilevel STATCOMs, designer’s role is to reduce the number of switching devices since, the total switching losses are proportional to the number of switching devices. The reduction in the count of switching devices also reduces the size and cost. In this paper, a five-level modified cascaded H-bridge inverter STATCOM is proposed for mitigation of harmonics. Modified Five-level CHB configuration is the most suitable as with lesser number of switches, give better performance resulting in a compact system. The PQ theory-based controller is developed for control of STATCOM operation. MATLAB simulation results are presented to demonstrate mitigation of harmonics.